Energy-Harvesting for IoT-based Wireless Nodes: A Progress Study - Abdul-Qawy, Antar Shaddad Hamed (Journal of Soft Computing and Data Mining, 2022)
Energy-harvesting technology is a promising renewable energy source for many applications through deriving energy from ambient environments. In IoT-based devices, this plays a significant role in providing sustainable energy and overcomes the need for battery maintenance and replacement, leading to increased efficiency, reliability, and operation time. This paper focuses on energy- harvesting in the context of IoT-based wireless nodes, its current progress, and future expectations. The main components, energy dissipations, and powering sources of IoT-based nodes are, first, identified. Then, the various ambient energy-harvesting sources and general architecture of the IoT-based energy-harvesting node are presented and concisely discussed. Finally, a progress discussion on the current and future trends of energy-harvesting technology for IoT devices is provided from different aspects, while shedding light on the key challenges facing the growth of energy harvesting for IoT-based systems. Overall, the paper provides a contemporary study that helps researchers who are working in this area and aiming to participate in its developments.